Unveiling the ultimate advantage: a meta-analysis of 3D visualization and problem-based learning in orthopedic education - Ting Li; Yidan Hu; Ruohong Song; Hangyu Liu; Xin Gao; Fei Wang; Chengwei Xiao; Xilin Liu (BMC Medical Education)
Abstract Background Three-dimensional (3D) visualization has become increasingly prevalent in orthopedic education to tackle the distinct anatomical challenges of the field. However, there is a conspicuous lack of systematic reviews that thoroughly evaluate both the advantages and drawbacks of integrating 3D with problem-based learning (3D + PBL). Methods A rigorous search of English databases (Cochrane Library, Embase, PubMed, Scopus, and Web of Science) and Chinese databases (National Knowledge Infrastructure: CNKI, Chongqing VIP: VIP, and Wan Fang) were performed up to July 2024 to identify relevant studies. Relevant studies were selected based on established eligibility criteria, with clinical data carefully extracted for analysis. Eighteen randomized controlled trials involving a total of 1,077 participants were included in the analysis. Results The findings indicated that 3D + PBL instruction significantly outperformed traditional lecture-based learning (LBL) in terms of theoretical knowledge (SMD = 1.62, 95% CI: 1.14–2.10, P < 0.00001) and practical operational scores (SMD = 2.29, 95% CI: 1.41–3.16, P < 0.00001). Furthermore, students exposed to 3D + PBL teaching exhibited a significantly better understanding of orthopedic anatomical structures compared to those receiving LBL (SMD = 1.18, 95% CI: 0.71–1.65, P < 0.00001). Additionally, students in the 3D + PBL group achieved higher theoretical grades (OR = 2.95, 95% CI: 1.57–5.55, P = 0.0008) and reported greater overall satisfaction (OR = 3.26, 95% CI: 1.91–5.54, P < 0.0001) compared to their LBL counterparts. Conclusion Given the unique demands of orthopedic education, 3D + PBL emerges as a highly effective teaching method. It not only improves students' theoretical scores but also enhances their communication skills and comprehension of complex concepts. Furthermore, students exhibit greater satisfaction with this approach.